Current Status and Future Prospect of Polymer-Layered Silicate Mixed-Matrix Membranes for CO2/CH4 Separation - Oh , P.C. (2016)
The mixed-matrix membrane (MMM), a state-of-the-art polymer-inorganic hybrid, is a relatively recent addition to the membrane family which adopts the synergistic advantages of the polymer and inorganic phase. Although marked improvement has been achieved by MMMs in CO2/CH4 separation, the development of a defect-free structure to transcend the Robeson upper bound limit remains a challenge. In previous years, a number of inorganic materials with diverse nature have been studied for CO2/CH4 separation; however, layered silicates have not attracted much attention despite their superior thermal and mechanical properties. Analyses of the potential of using layered silicates as inorganic fillers in MMM fabrication for CO2/CH4 separation are reviewed. Additionally, the immediate challenges toward successful formation of layered silicate-based MMM and future prospects are addressed.